INFLUENCE OF FOREST STAND DENSITY ON PINUS SYLVESTRIS ROUNDWOOD QUALITY IN EVEN-AGED MIXED SCOTS PINE STANDS IN MYRTILLOSA MEL. MESOTROPHIC SITE TYPE (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2021)
Among different development directions for better forest utilization, the purposefully detailed assessment of wood quality as raw material, faciliating improved wood utilization in manufacturing of traditional roundwood products as well as brand new products, proves to be very perspective. Roundwood quality features substantially differ depending on forest stand geographic location, growing site conditions, tending of forest stands and other circumstances [2], [3], [11]. Therefore, the economical estimation of more important tree species in Latvia should not be based only on scientific conclusions made in other countries, so particular research is needed for this purpose. Pine (Pinus sylvestris) is the most widespread tree species in Latvia, therefore a research work provided the characteristic of round wood obtained from pine tree stem is an actual point from several aspects, as it is necessary;to create early prediction models of roundwood quality; to plan harvesting purposes;to create the data basis of economically more relevant domestic tree species;to provide the further development of roundwood quality assessment methods;to estimate the competitiveness of Latvia pine timber in the world marketThe main goal of study is to work out the quality characteristic of pine roundwood manufactured in final felling sites depending on timber formation damages- bark abrasion caused side drought.